(3JbQjH GdfTQ aj GdbQGAGJ GdYTQs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj , (B833 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg Ydi GdJbQjH hGdJjSjQ hHYO adeG cfG cJGH fTQ GdbQGAGJ GdYTQI (B( (3cPG (B) (3eeG YQa bOQg hGTJgQ Hjf GdWdHI PcQg ZjQ Cfg aj GdESgGH hGdCWfGH QHeG YQJ (B( (3cPG (B) (3JfGhdg Ydi HYV GdCUMGH GdJeS efj Gf GbQHg hCjSQ Hg hCbJUQg Ydi eG ajg ef GdNdGa hjchf fTQG ddWjHI hjSjQG dcdeGJ GdWjHIs
(3BNQgG (B:s
(3Qhi CHh efUhQ GdGQLGfj aj cJGHg aVGFd GdbQBf Yf OGhO Hf bjS bGd (B: (3cGf QShd Gddg Udi Gddg Ydjg hSde jbhd (B- (3YfO NJe GdbQBf (B- (3Gddge GQMefj HGdbQBf GdYXje hGLYdg dj GeGe hfhQG hgOi hQMeI Gddge PcQfj efg eG fSjJ hYdefj eG LgdJ hGQRbfj JdGhJg BfGA Gddjd hGdfgGQ hGLYdg dj MLI jGQH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 45s
(3eYLe GdeDdajf (B3 / 687s
(3cTa GdXfhf (B2 / 1952s
(3TPQGJ GdPgH (B7 / 204s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs